Spatiotemporal patterns of macroinvertebrate functional habit groups in response to seasonal variations and anthropogenic pressures in the Martil Basin, Morocco - ACHRAF GUELLAF; KAWTAR KETTANI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Guellaf A, Kettani K. 2025. Spatiotemporal patterns of macroinvertebrate functional habit groups in response to seasonal variations and anthropogenic pressures in the Martil Basin, Morocco. Biodiversitas 26: 3227-3236. Trait-based analysis of macroinvertebrates offers a comprehensive perspective for monitoring the integrity of aquatic ecosystems. This study examined the functional responses of macroinvertebrates to anthropogenic pressures and seasonal changes in the Martil Basin, Northwestern Morocco. Analyses were based on physicochemical and bacteriological variables (temperature, pH, electrical conductivity, dissolved oxygen, BOD5, COD, TSS, Fecal coliforms, and Fecal streptococci), alongside hydro-morphological factors (current speed, water depth, and stream width). Macroinvertebrates and water were sampled over an annual cycle (spring, summer, autumn of 2017, and winter of 2018) at nineteen sites. The Functional Habit Group (FHG) composition varied significantly across sites and seasons. The abundance and taxa richness were highest in spring, with clingers being the most abundant group. Multivariate analyses revealed distinct upstream-downstream gradients, with sensitive taxa dominated by clingers correlated with high dissolved oxygen levels and low pollution levels in upstream areas. In contrast, tolerant taxa such as burrowers and swimmers dominated downstream sites impacted by agricultural runoff and urban pollution. A deeper understanding of the functional traits of macroinvertebrates and their responses to anthropogenic and environmental stressors can serve as a valuable tool for scientists and managers, providing complementary indicators for the development of biomonitoring frameworks and the preservation of aquatic biodiversity.